A randomized clinical trial for the assessment of the efficacy and safety of guluronic acid (G2013) in patients with rheumatoid arthritis. (2nd January 2019) - Khadem Azarian, Shahin; Akhlaghi, Maassoumeh; Mahmoudi, Mahdi; Mostafaei, Shayan; Jamshidi, Ahmad Reza; Nazeri, Sepideh; Mirshafiey, Abbas
Abstract: Objective: To evaluate the safety, efficacy and tolerability of guluronic acid (G2013) in order to treat the rheumatoid arthritis patients who had inadequate response to conventional drugs. Methods: A randomized, 12-week clinical trial with two treatment arms: guluronic acid (G2013) and conventional treatment was performed. The diagnosed RA patients according to the ACR/European League against Rheumatism 2010 classification criteria, with an active disease at baseline that had inadequate response to conventional therapy were considered for the study. G2013 was administered orally twice a day with capsules of 500 mg during a period of 12 weeks and the patients were followed up for the safety and efficacy. Results: Our data showed that, the mean changes in the G2013 and control groups were −7.54 and −2.5 for tender joint count; −7.59 and −3.59 for swollen joint count; −30 and −0.9 for physician global assessment; −23.18 and −1.81 for patient global assessment; −14.45 and −1.45 for erythrocyte sedimentation rate, respectively. Improvements seen with G2013 were significantly greater than those with conventional drugs. In total, in 15.3% of G2013-treated patients and 69.2% of conventional-treated patients adverse events (AEs) occurred in this study. Conclusion: These data from routine rheumatology clinical practice highlight the effectivenessof G2013 in combination with conventional therapy with more desirable safety profile compared to the conventional-treated patients. Therefore, G2013 therapy could be an appropriate choice in order to manage the RA disease. (Clinical trial identifier: IRCT2016092813739N5).